Design of Microstrip-Embedded Building Structure Antenna for Smart City IoT Networks - LOMPO RAMOS EMAKARIM; NURMAYANTI ZAIN; FARHAN REZKI ARIFIN; MUH. IRHAM M; UMMU KHALSUM; ABDUL HAKIM UDIN (Institut Teknologi Nasional, Bandung, 2026)
Building-integrated antenna technology offers a promising approach for IoT deployment in smart city. This study proposes a conceptual framework for microstrip antenna embedded within metal structural elements. It aims to analyze the electromagnetic behavior and performance of these antennas for IoT applications. The methodology combines analytical modeling with HFSS simulations to evaluate key parameters including return loss, VSWR, gain, and radiation patterns within the 700 MHz sub-GHz IoT bands. Simulation results demonstrate that the concrete column structure supports effective antenna operation, achieving a return loss of -17.15 dB and a VSWR of 1.32. Despite the inherent attenuation, the antenna maintains a positive realized gain of 1.44 dBi and a sufficient broadside radiation pattern. The study concludes that such embedded antennas offer a viable solution for smart city IoT infrastructure.